Task Group 174 Report: Utilization of [18F]Fluorodeoxyglucose Positron Emission Tomography ([18F]FDG‐PET) in Radiation Therapy. Issue 10 (6th September 2019) - Das, Shiva K.; McGurk, Ross; Miften, Moyed; Mutic, Sasa; Bowsher, James; Bayouth, John; Erdi, Yusuf; Mawlawi, Osama; Boellaard, Ronald; Bowen, Stephen R.; Xing, Lei; Bradley, Jeffrey; et al.
Abstract : The use of positron emission tomography (PET) in radiation therapy (RT) is rapidly increasing in the areas of staging, segmentation, treatment planning, and response assessment. The most common radiotracer is 18 F‐fluorodeoxyglucose ([ 18 F]FDG), a glucose analog with demonstrated efficacy in cancer diagnosis and staging. However, diagnosis and RT planning are different endeavors with unique requirements, and very little literature is available for guiding physicists and clinicians in the utilization of [ 18 F]FDG‐PET in RT. The two goals of this report are to educate and provide recommendations. The report provides background and education on current PET imaging systems, PET tracers, intensity quantification, and current utilization in RT (staging, segmentation, image registration, treatment planning, and therapy response assessment). Recommendations are provided on acceptance testing, annual and monthly quality assurance, scanning protocols to ensure consistency between interpatient scans and intrapatient longitudinal scans, reporting of patient and scan parameters in literature, requirements for incorporation of [ 18 F]FDG‐PET in treatment planning systems, and image registration. The recommendations provided here are minimum requirements and are not meant to cover all aspects of the use of [ 18 F]FDG‐PET for RT.